Pengaruh Reward terhadap Kepuasan Kerja Karyawan PDAM Magetan - Lailatul Muqoyyaroh . (Universitas PGRI Madiun, 2018)
This research has purpose to know giving reward at PDAM Magetan, to know employee job satisfaction at PDAM Magetan, and to know influence of reward to employee job satisfaction at PDAM Magetan. Sampling technique in this research using simple random sampling technique taken 66 employees at PDAM Magetan. Data were taken by questionnaire, observation and documentation. The analysis was processed by SPSS version 16.0 using simple linear regression with test test and test hypothesis test. The results showed that the result of Simple Linear Regression Test is Y = 13.054 + 0.496, it means that if the variable of customer satisfaction is constant or constant, then the amount of job satisfaction of employee is 13,054. The result of Coefficient of Determination (R ^ 2) is known 0,879 indicates that 87% variable of employee job satisfaction influenced by reward, while the rest 13% influenced by other variable. Furthermore, the result of t test obtained t_hitung value is 21,549 while t_tabel equal to 1,668. This means that the value of t _count > t_tabel (21,549 > 1,668) so it can be concluded that Ho is rejected and Ha accepted, it means there is influence between Reward on Job Satisfaction Employees At PDAM Magetan.